An enlarged circumscription of Bifrenaria (Orchidaceae: Maxillariiinae) - Meneguzzo, Thiago E. C.; Chase, Mark W. (Phytotaxa, 2024)
A revised delimitation of Bifrenaria broadens the genus to include the previously accepted genera Guanchezia, Horvatia, Hylaeorchis, Rudolfiella, Scuticaria, and Teuscheria. These genera as currently circumscribed are changed to sections, and their respective species transferred or combined along with newly synonymised species. Bifrenaria sect. Stenocoryne and B. sect. Adipe are reinstated, Adipe treated as section, and two new sections are described, as follows: B. sect. Integrilabellae and B. sect. Xylobioides.